Optimalisasi Pembatasan Dana Kampanye Pemilihan Umum: Studi Perbandingan Indonesia dan Selandia Baru - Taniady, Vicko (Universitas Islam Malang, 2021)
Election attendance is not complete without campaign activities. The campaign itself is a form of a dialogue between the candidates and the public. However, campaign attendance has had problems since the start of the election. The purpose of this study is to examine the implementation and regulations related to campaign finance in Indonesia. The research method used is a qualitative method using a comparative study approach with New Zealand and normative juridical and using library research techniques to find secondary data. The discussion of this discussion suggests that campaign finance policies in Indonesia are still not comprehensive. This is a trigger for acts of corruption and undermines the democratic order in Indonesia. This can be seen from the absence of binding regulations regarding the expenditure of personal and political funds in campaign activities. Compared to New Zealand, the country has a comprehensive policy by implementing other laws and regulations, political arrangements for campaign funds from candidates, third parties, and individuals, groups, or companies. Therefore, by looking at the policies issued by New Zealand, the Indonesian government can review the policies carried out by that country